An Adaptive Physiologically Based Pharmacokinetic–Driven Design to Investigate the Effect of Itraconazole and Rifampicin on the Pharmacokinetics of Molibresib (GSK525762) in Healthy Female Volunteers. (20th August 2020) - Riddell, Kylie; Patel, Aarti; Collins, Gary; Zhou, Yanyan; Schramek, Dan; Kremer, Brandon E.; Ferron‐Brady, Geraldine
Abstract: Molibresib (GSK525762), an orally bioavailable small molecule with 2 major equipotent active metabolites, is being developed for the treatment of cancers. Molibresib is a substrate of cytochrome P450 (CYP) 3A4 and P‐glycoprotein (P‐gp). To enable administering safe doses of molibresib to healthy volunteers, this 2‐part randomized, open‐label, crossover drug‐drug interaction trial was conducted as an adaptive design study using physiologically based pharmacokinetic (PBPK) modeling and simulation to predict the lowest doses of molibresib that could be safely administered alone (10 mg) or with itraconazole and rifampicin (strong inhibitors and inducers of CYP3A and P‐gp, respectively). PBPK simulation guided the molibresib dose (5 mg) to be administered along with itraconazole in part 1. Itraconazole increased total exposure (AUC) of molibresib by 4.15‐fold with a 66% increase in Cmax, whereas the total AUC and Cmax for the 2 major active metabolites of molibresib decreased by about 70% and 87%, respectively. A second PBPK simulation was conducted with part 1 data to also include the active metabolites to update the recommendation for the molibresib dose (20 mg) with rifampicin. With rifampicin, the AUC and Cmax of molibresib decreased by approximately 91% and 80%, respectively, whereas the AUC of the 2 active metabolites decreased to a lesser extent (8%), with a 2‐fold increase in Cmax . The results of this study confirmed the in vitro data that molibresib is a substrate for CYP3A4. The adaptive design, including Simcyp simulations, allowed evaluation of 2 drug interactions of an oncology drug in a single trial, thus minimizing time and exposures administered to healthy subjects.